Diversity and Status of Butterflies in Lowland Districts of West Nepal - Khanal, Bhaiya (Journal of Natural History Museum, 2009)
This paper is an outcome of the studies made in four districts (Dangdeukhuri, Banke, Bardia and Surkhet) of western Terai in different months of various years. Altogether 85 species categorized into 64 genera and 10 families have been reported with their status categories based on national status list. The process of urbanization has altered valuable natural habitats of many of the rare species especially in Banke and Dangdeukhuri districts. Monitoring process under the established regulation and thorough investigations in many unexplored areas of this region have been felt essential so to design suitable conservation measures to butterflies of this region. Key words: Biodiversity; western terai; butterflies; unexplored; habitats Journal of Natural History Museum Vol. 23, 2008 Page 92-97